Geographic proximity to local governments and corporate energy efficiency: evidence from Chinese industrial enterprises - Rui Zhang; Kejin Ni; Lei Tan (Frontiers in Environmental Economics)
IntroductionThis study investigates the role of geographic proximity to local environmental protection agencies (EPAs) in enhancing firms' energy efficiency. It explores how environmental pressure and green innovation are influenced by spatial dynamics, providing new insights into the Porter hypothesis.MethodsThe analysis utilizes energy consumption and geographic data from Chinese industrial firms. A combination of statistical and econometric methods is employed to evaluate the relationship between proximity to EPAs and energy efficiency, including heterogeneity analysis across firm ownership types.ResultsThe findings reveal that firms located closer to EPAs exhibit higher energy efficiency, primarily due to increased regulatory pressure that fosters green innovation. This positive effect is most pronounced within a 60 km radius, diminishing beyond this range. Heterogeneity analysis indicates stronger effects for private and mixed-ownership firms compared to state-owned and multinational firms.DiscussionThe study underscores the nuanced interplay between geographic proximity, regulatory frameworks, and green innovation. It highlights how targeted environmental policies can drive corporate energy efficiency improvements, offering valuable implications for optimizing regulatory designs.